Ten Years of JIBS at Rutgers Graduate School of Management - Dymsza, William A. (Journal of International Business Studies, 1984)
With the Winter 1984 issue of JIBS, Rutgers Graduate School of Management completes 2 terms or 10 years of publication of JIBS. This has been a challenging but rewarding experience for me and my staff at Rutgers. We take pride in the progress we have achieved after starting with meager and inadequate resources to make the Journal of International Business Studies the outstanding refereed professional journal in the field. This achievement was possible only through the dedicated efforts and cooperation of several score of individuals – more than we can mention in this note – including our small staff, members of the Editorial Board, Section and other Editors, other reviewers, many officers of the Academy of International Business, authors who submitted manuscripts, and various scholars who advised us on the editorial policies and thrust of the Journal.